Effects of Gd3+ doping on structural and dielectric properties of PZT (Zr:Ti = 52:48) piezoceramics - L. Pdungsap (2018)
The purpose of this research is to study the effect of doping Gd into Pb(Zr0.52Ti0.48)O3 ceramics prepared by solid state reaction. X-ray diffraction patterns show that all PGZT samples are of tetragonal structure and the highest doping should be no more than 2 mole∈% Gd at which the unreacted oxides start to appear. The electron spin resonance (ESR) spectra of PGZT's indicate that Gd3+ can enter both A site of the perovskite structure instead of only A site as widely believed. The ESR peaks resonance shift towards low fields as the concentration is higher, which is due to the change in crystal field experienced by Gd3+ ions. At x =0.001, 0.005 and 0.01 dopings, two sets of powder ESR signals arising from Gd3+ (4f7, spin 7/2) ions at A site. The first set shows some fine structure having strong absorption peaks centered at 76.26 mT (g = 8.550). The second is a seven-peak spectrum centered at 206.01 mT (g = 3.165), which belongs to the Gd3+ ions at B sites. Furthermore, the overlapped ESR strong absorption peaks from 309.17 mT to 314.49 mT (g = 2.2818-2.1087) belong to Gd3+ of unreacted Gd2O 3. The local environments of Gd3+ ions were verified from the calculated ESR spectra using appropriate spin Hamiltonian parameter, i.e. gyromagnetic tensor g, zero-field splitting D and hyperfine tensor A.